The Word “Translation” And its Semantics in the Arabic Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the semantics of the word “translation” in the Arabic language, exploring its etymology and diverse meanings. Drawing from classical sources like Lisan al-Arab and Al-Qamus, it identifies four core interpretations: message conveyance, clarification, cross-linguistic expression, and direct translation. The paper categorizes translation into two types literal and explanatory highlighting their distinct approaches and challenges. Effective translation requires linguistic proficiency, cultural awareness, and fidelity to the original's intent. This analysis underscores the complexity of translation and its role in bridging linguistic and cultural divides